NUMERICAL SOLUTIONS OF COVID-19 SIRD MODEL IN NIGERIA (FUDMA JOURNAL OF SCIENCES, 2022)
A mathematical model of the Susceptible, Infectious, Recovery and Death (SIRD) for the spread of the COVID-19 disease in Nigeria was considered in this paper. The model values and parameters were obtained from Nigeria Centre for Disease Control Coronavirus COVID-19. The model was solved using Heun's method and Runge-Kutta's method of orders four and five to obtain an approximated solution for the model with the help of the Matlab Program.  The result obtained was illustrated in plots to show the progression of the disease in the various classes. The comparisons of the three numerical methods used correspond well with each other by showing the same behavior pattern
Keywords: COVID-19, Nigeria, SIRD, Heun’s method, Fourth-order Runge-Kutta method, Fifth-order Runge-Kutta method, Matlab,